CURRENT PROBLEMS AND RESOLUTIONS OF TEACHING ENGLISH - Utekova Gulzar Sarsenbaevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Teaching grammar has been regarded as crucial to the ability to use language. For this reason, this article introduces a five-step procedure for teaching grammar.